The perception towards practicum experience among Islamic education preservice teachers in University Sultan Zainal Abidin (UnisZA), Terengganu, Malaysia - Abdul Hakim, Abdullah; Mustafa, Che Omar; Rahimah, Embong; Nor Suhaily, Abu Bakar (2015)
The purpose of this study is to examine the perception of Islamic Education preservice teachers in Universiti Sultan ZainalAbidin (UniSZA), Terengganu, Malaysia on their practicum experience from the very important aspects of teacher education which include positive attitudes andprofessional skills development. This study also tried to scrutinize the potential problems encountered during their practicum. This quantitative study used questionaireedited and approved by a team of experts in the field as an instrument for collecting data and involved all final year students (n=55) from Bachelor in Islamic Education who were engaged in the practicum at 19 schools for 4 months. The data was then analysed using the Statistical Package for Social Sciences (SPSS) version 12.0. The “Realibility Analysis-Scale Alpha” test was carried out on all items in the questionnaire with a result of 0.86 which indicates a high level of reliability. The results showed that all the respondents were of the opinion that the practicum experience had successfully developed their positive attitudes as well as increased their professional skills. The study also found that the respondents did not encounter any significant problems during their practicum. Hence, this study suggests that UniSZA can carry on with its effort to train prospective Islamic Education teachers and share its expertise with other teacher training agencies in order to fullfil the nation’s requirements.